ICTV Virus taxonomy profile: Alphaflexiviridae - Kreuze, Jan F.; Vaira, A.M.; Menzel, W.; Candresse, T.; Zavriev, S.K.; Hammond, John; Ryu, K.H. (Microbiology Society, 2020)
The family Alphaflexiviridae includes viruses with flexuous filamentous virions that are 470–800 nm in length and 12–13 nm in diameter. Alphaflexiviruses have a single-stranded, positive-sense RNA genome of 5.5–9 kb. They infect plants and plant-infecting fungi. They share a distinct lineage of alphavirus-like replication proteins that is unusual in lacking any recognized protease domain. With a single exception, cell-to-cell and long-distance movement is facilitated by triple gene block proteins in plant-infecting genera. This is a summary of the International Committee on Taxonomy of Viruses (ICTV) Report on the family Alphaflexiviridae, which is available at www.ictv.global/report/alphaflexiviridae.